Stakeholders’ Management Approaches in Construction Supply Chain: A New Perspective of Stakeholder’s Theory - Shahbaz, Muhammad Saeed; Chandio, Abdul Fattah; Oad, Mehboob; Ahmed, Arslan; Ullah, Rizwan (International Journal of Sustainable Construction Engineering and Technology, 2018)
Construction is dependent on accurate, timely and safe supply chain, otherwise whole project will be halted. Previously, it has found that most construction projects failed to complete on designated time that ultimately surges the cost as well. Although there are various approaches to deal with the situation, there is evidence that collaboration among stakeholders would reduce the risks and enhance the performance. Therefore, the aim of this study is to verify the relationship between the supply chain performance (SCP) with three stakeholder management approaches, namely supplier relationship (SR), customer relationship (CR), and risk and reward sharing (RRS). A total of 585 questionnaires were distributed using systematic probability sampling of listed construction organizations and only 258 responses were returned. The data were analyzed through the Smart PLS Software using two types of function i.e. PLS Algorithm and Bootstrapping. Based on the PLS Algorithm, the path coefficient results confirm that SR, CR, and RRS influence the SCP. It also has found that all three approaches have 56% of explaining power on SCP (R2 value = 0.560). The bootstrapping function revealed that the three hypotheses supported and this confirmed the hypotheses are true. This study enhances the relationship among stakeholders beyond the traditional collaboration to risk and reward sharing simultaneously. This integration will provide a competitive position as all members share their expertise that will ultimately improve the quality and lead time and enrich the flexibility. Thus, it can be concluded that long-term success is heavily dependent on relationships with the suppliers, customers, risk and reward sharing. This study will help construction managers to understand the importance of good relationships while doing strategic decision making.